Effect of Prophylactic Levosimendan on All-Cause Mortality in Pediatric Patients Undergoing Cardiac Surgery—An Updated Systematic Review and Meta-Analysis - Wang, Hongbai; Luo, Qipeng; Li, Yinan; Zhang, Liang; Wu, Xie; Yan, Fuxia (Frontiers in Pediatrics, 2020)
Background: Levosimendan, a calcium sensitizer, enhances the myocardial function by generating more energy-efficient myocardial contractility than achieved through adrenergic stimulation with catecholamines. We conducted this meta-analysis to primarily investigate the effects of levosimendan on all-cause mortality in pediatric patients undergoing cardiac surgery under cardiopulmonary bypass. Methods: The databases of Pubmed, Embase and Cochrane Library were searched till 21st March 2020. The eligible criteria were participants with age<18 yr and undergoing cardiac surgery for congenital heart disease (CHD), and studies of comparison between levosimendan and placebo or other inotropes. Stata version 12.0 was used to perform statistical analyses. Results: 6 Randomized Controlled Trials (RCTs) and 1 Case-Control Trial (CCT) including 436 patients were included. The results showed that levosimendan did not significantly decrease all-cause mortality compared with control drugs (and placebo) in children undergoing cardiac surgery (P =0.403). Perioperative prophylactic levosimendan administration strikingly decreased the low cardiac output syndrome (LCOS) incidence (P=0.016), but did not significantly reduce acute kidney injury (AKI) incidence (P=0.251), and shorten mechanical ventilation and ICU stay time compared with other inotropes and placebo by analyzing the included literatures [mechanical ventilation (or intubation) time: P=0.188; ICU stay time: P=0.620]. Conclusions: Compared with other inotropes and placebo, perioperative prophylactic administration of levosimendan did not decrease rates of mortality and AKI and shortening the time of mechanical ventilation (or intubation) and ICU stay, but demonstrated significant reduction in LCOS incidence after corrective surgery in pediatric patients for CHD. Due to limited number of included studies, the current data were insufficient to make the conclusions.